Frequency of Preterm Birth in Females Diagnosed with Urinary Tract Infection during 2nd Trimester - Samia Rafique, Ayesha Abdul Sattar, Madiha Fatima, Sumaira Nadeem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preterm birth is also associated with infections such as urinary tract infection. Aim: To find frequency of preterm birth in females diagnosed with urinary tract infection during 2nd trimester. Study design: Cross sectional study. Methodology: Total of 338 cases meeting inclusion criteria were enrolled through non-probability consecutive sampling from OPD of Obs and Gynecology department of Jinnah Hospital Lahore for duration of 06 months. Their basic information like age, parity, gestational age at diagnosis of UTI was taken after taking an informed consent. All diagnosed case of UTI was treated with standard protocol and then females were followed up till their delivery. Data was evaluated by using SPSS v.24. Quantitative data was presented as mean ± SD. Qualitative data was presented as frequency and percentage. Chi-square test was applied with P-value ≤0.05 taken as significant. Results: In this study, mean gestational age at time of UTI diagnosis was 19.93 ± 4.14 weeks with minimum and maximum gestational age as 13 and 27 weeks. According to operational definition, preterm birth was noted in 100(29.59%) of the females while in 238(70.41%) females had term delivery. Practical Implication: As there was limited local data regarding this common health issue and lack of followed-up specifically to see frequency of preterm birth among pregnant females having UTI at our clinical set-ups thus results of this study helped to identify higher preterm birth rate in future among females presenting with UTI thus proper management can minimize the risk of preterm birth. Conclusion: It was concluded that a high number of females had preterm birth after diagnosis of UTI. Hence, in future females having UTI need more attention to reduce the risk of preterm birth. Keywords: Urinary Tract Infection, Pregnancy, Gestational Age, 2nd Trimester and Preterm Birth.